Improving the efficiency of vegetable oil extraction by biocatalytic treatment of oilseed raw materials - Nekrasov, P. O.; Berezka, T. O.; Nekrasov, O. P.; Gudz, O. M.; Molchenko, S. M. (Oles Honchar Dnipro National University, 2025)
Conventional technology for processing vegetable oilseeds is typically characterized by exposing the processed product to intense heat and humidity. Such methods have an adverse effect on the beneficial components of oil-containing raw materials, irreversibly degrading the quality and yield of the resulting product, while increasing the cost of edible oil production. The above drawbacks can be eliminated through preliminary enzymatic treatment of oilseed raw materials. Owing to their protein nature, enzymes operate under mild conditions, increasing the yield of finished products, improving their quality and nutritional value. This paper suggests an improved method for preparing sunflower seed meats for pressing by treating it with a complex of enzyme agents such as Alcalase 2.4 L FG and Viscozyme L. To analyze the collected data and optimize the parameters, the response surface methodology was chosen based on the central composite rotational design. This research has shown the feasibility of using a hydrolase complex in preparing sunflower seed meats for oil extraction aimed at increasing the efficiency of the pressing process. A mathematical model has been designed to predict the oil yield based on the parameters of biocatalytic raw material treatment. We found the most suitable parameters for obtaining the maximum oil yield: the enzyme complex content was 0.37 % by the meats weight; the temperature was 57 °C; and the duration of meats treatment was 115 minutes. Under these predictor values, the product yield was 77.3 % ± 1.4 % of the total oil content of the raw material, which is almost 16 % higher than the average value of this figure for control experiments not subjected to enzymatic treatment.

Традиційна технологія переробки рослинної олійної сировини характеризується застосуванням інтенсивних теплових і вологотеплових впливів на оброблюваний матеріал. Використання таких методів негативно впливає на корисні компоненти олієвмісної сировини, незворотно знижуючи якість і вихід отриманого продукту поряд із збільшенням витрат на виробництво харчових олій. Зазначені недоліки усуваються у разі попередньої ферментативної обробки олійної сировини. Завдяки своїй білковій природі ферменти працюють у м’яких умовах, збільшуючи вихід готової продукції, підвищуючи її якість і харчову цінність. У роботі запропоновано удосконалений метод підготовки м’ятки насіння соняшнику до пресування шляхом її обробки комплексом ферментних препаратів Alcalase 2.4 L FG та Viscozyme L. Для аналізу отриманих у ході досліджень даних та оптимізації параметрів було обрано методологію поверхні відклику із використанням центрального композиційного ротатабельного плану. У результаті дослідження показана доцільність використання комплексу гідролаз у підготовці м’ятки насіння соняшника до вилучення олії з метою підвищення ефективності процесу пресування. Розроблено математичну модель, яка дозволяє на основі даних щодо параметрів біокаталітичної обробки сировини прогнозувати вихід олії. Встановлено оптимальні параметри, які дають можливість отримати максимальний вихід олії: кількість ферментного комплексу – 0.37 % від маси м'ятки, температура – 57 °С, тривалість обробки м’ятки – 115 хвилин. Вихід продукту за вказаних значень предикторів становив 77.3 % ± 1.4 % від загальної олійності сировини, що майже на 16 % більше, ніж середнє значення даного показника для контрольних дослідів, в яких зразки не піддавали ферментативній обробці.
Підвищення ефективності вилучення рослинної олії шляхом біокаталітичної обробки олійної сировини
Keywords: meats; hydrolase complex; biocatalysis; optimization; rotational design; м'ятка; комплекс гідролаз; біокаталіз; оптимізація; ротатабельний план